INDONESIA’S ECONOMIC INTEREST IN RICE TRADE COOPERATION WITH THAILAND 2019-2022 - Rizfi Nur Rohim; Ramadhony, Farid (Moestopo International Review on Social, Humanities, and Sciences, 2025)
Indonesia is an agrarian country where a majority of its population relies on agriculture or farming Rice, a native plant of Asian countries including Indonesia, is a significant agricultural product Additionally, many Indonesians believe that rice is a gift from the Almighty Creator, serving as a source of life and well-being for humanity. This research discusses Indonesia’s Economic Interest in Rice Trade Cooperation with Thailand in 2019-2022. The main objective of this research is to analyze and identify the economic benefits that can be obtained by Indonesia through rice import trade cooperation with Thailand. The research method used is a qualitative method with descriptive research type and data search technique by collecting data through literature study and analysis of relevant secondary data. This research uses Hans. J. Morgenthau’s interest theory. Based on the results of the study, it was found that rice trade cooperation with Thailand has economic interest for Indonesia that can be help diversify rice supply in Indonesia, reduce dependence on one exporting country, and reduce the risk of unstable supply. In this context, cooperation with Thailand can provide a diverse and secure alternative supply of rice. This study also underlines the importance of maintaining a balance between imports and domestic rice production.